KRITIK KONSEPTUAL ATAS TERMINOLOGI ISLAM NUSANTARA: KAJIAN LEKSIKAL DAN HISTORIS DALAM WACANA STUDI AGAMA - Haqq, Muhammad Valiyyul (Integritas Terbuka: Peace and Interfaith Studies, 2025)
This study critically examines the term Islam Nusantara as a key concept in Indonesia’s discourse on Islamic moderation. Nahdlatul Ulama popularized the term to articulate a form of Islam that integrates Islam’s universal values with local cultural contexts. This study aims to assess the conceptual precision of Islam Nusantara by analyzing its lexical and historical implications, given its expanding use across religious discourse, academic debates, and public policy. The study employs a qualitative approach grounded in lexical-semantic analysis and historical-conceptual inquiry. It draws on library research by conducting a critical reading of religious texts, organizational documents, public speeches, and academic literature that represent the pro-and-con debates surrounding Islam Nusantara. First, at the lexical level, the phrase Islam Nusantara contains inherent ambiguity because its grammatical structure permits an attributive reading—Islam that is Nusantaran—which can prompt audiences to interpret it as a particular variant or typology of Islam rather than as a designation of the geographic and cultural context of Islamic practice. Second, at the historical level, the narratives that sustain the term tend to treat Javanese–Malay Islam as the dominant representation of Islam in the archipelago, thereby obscuring the plurality of routes, agents, and Islamic traditions across Indonesia’s islands. Third, at the discursive level, Islam Nusantara functions primarily as a discursive strategy and a project of religious identity through which actors articulate Islamic moderation in the context of nationhood and globalization, rather than as a stable normative theological category. These findings underscore the need for conceptual caution in deploying religious terminology so that it does not generate semantic reduction or symbolic exclusion. The study’s original contribution lies in formulating a framework for terminological critique that positions Islam Nusantara as an arena of meaning negotiation between Islam’s universality and cultural locality, while opening space for the development of a concept of Islamic moderation that is more academically precise and historically inclusive.